ANALISIS KEBIJAKAN 5C DENGAN MENGGUNAKAN METODE ANALYTIC NETWORK PROCESS - ", Muslimawati; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
5C‟s Analysis policy are extension of credit principles for banking industry. At PT. Bank Riau Kepri Domestic Branch Rumbai, Pekanbaru, this analysis are main principles for credit implementation for new client and beside that five analysis, PT. Bank Riau Kepri used The Letter of Management Decision No. 96/ KEPDIR/2009 as it orientation too.This research are purpose to knowing about 5C‟s analysis policy implementation by using analytic network process (ANP) method. In this research, the data used are primary data. Primary data was obtained from indepth interview with expert and practitioners that have more experiences about 5C‟s Analysis policy. Then, they have to answer some questioner at second meeting.The results show that from the five analysis policy instrument which character, capital, capacity, collateral and condition of economy is character. Character is main appraisal principles in 5C‟s analysis policy implementation. It showed that between expert/ academics and practitioners relatively dissents in their opinion related appraisal the 5C‟s analysis policy at PT. Bank Riau Kepri domestic branch Rumbai, Pekanbaru.Keyword : Policy Analysis, 5C‟s Analysis, A